2022
DOI: 10.3390/nano12030388
|View full text |Cite
|
Sign up to set email alerts
|

Study Effect of nAg Particle Size on the Properties and Antibacterial Characteristics of Polysulfone Membranes

Abstract: Polysulfone ultrafiltration membranes were fabricated using various sizes (20, 40, and 90–210 nm) of silver nanoparticles (nAg) blended in a dope solution. To characterize the performance and properties of the prepared membranes, scanning electron microscopy (SEM), water contact angle, protein separation, water flux, and antibacterial tests were conducted. The characterization results revealed that when nAg particles (20 nm) were blended into the base polymer PSF, the PSF/nAg blended membrane had the lowest co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…As well as the antibacterial effect, the size of Ag NPs was studied in the fabrication of the polysulfone ultrafiltration membrane. In a recent study of Prihandana et al [ 45 ], Ag NPs in three dimensions were integrated in the membrane phase inversion fabrication method in order to observe the effects on the pore dimensions and the hydrophilicity of the final material. The contact angle analysis performed showed that, by comparing the control with the three membranes based on Ag NPs, the hydrophilicity is improved when the smallest nanoparticles (20 nm) are integrated.…”
Section: Silver Nanoparticles Particularities Related To Shape Size A...mentioning
confidence: 99%
See 1 more Smart Citation
“…As well as the antibacterial effect, the size of Ag NPs was studied in the fabrication of the polysulfone ultrafiltration membrane. In a recent study of Prihandana et al [ 45 ], Ag NPs in three dimensions were integrated in the membrane phase inversion fabrication method in order to observe the effects on the pore dimensions and the hydrophilicity of the final material. The contact angle analysis performed showed that, by comparing the control with the three membranes based on Ag NPs, the hydrophilicity is improved when the smallest nanoparticles (20 nm) are integrated.…”
Section: Silver Nanoparticles Particularities Related To Shape Size A...mentioning
confidence: 99%
“…The contact angle analysis performed showed that, by comparing the control with the three membranes based on Ag NPs, the hydrophilicity is improved when the smallest nanoparticles (20 nm) are integrated. The size-dependent aspect was also proved in the evaluation of the antimicrobial activity of the membranes, where Ag NPs at 20 nm and 40 nm showed better bactericidal effects compared with the ones found in 90–210 nm [ 45 ].…”
Section: Silver Nanoparticles Particularities Related To Shape Size A...mentioning
confidence: 99%
“…Other manufacturing techniques as supercritical CO 2 -assisted processes, 3D printing, porogen leaching, gas foaming, phase separation, or any possible combination between these may also be employed for polymeric membrane preparation [ 63 , 64 ]. Among these techniques, the phase separation process is easy to execute and does not require sophisticated equipment.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that the toxicity of AgNPs was related to their particle size, and small particles were more toxic to organisms [ 9 , 20 , 33 ]. In our experiments, the core size of AgNPs did not change significantly, while the hydrodynamic diameter increased in 10% of Hoagland’s solution, indicating an AgNP aggregation in the solution.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their excellent antibacterial properties, silver nanoparticles (AgNPs) are widely used in various fields, including antibacterial coatings, medical machinery, cosmetics, clothing, food packaging, plastic products, detergent, paint, and some porous structures [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In the process of production, application, and recovery, AgNPs can be discharged into environments in many ways.…”
Section: Introductionmentioning
confidence: 99%